Crystallization and preliminary X-ray diffraction characterization of the XccFimXEAL-c-di-GMP and XccFimXEAL-c-di-GMP-XccPilZ complexes from Xanthomonas campestris - Liao, Yi-Ting (2013)
c-di-GMP is a major secondary-messenger molecule in regulation of bacterial pathogenesis. Therefore, the c-di-GMP-mediated signal transduction network is of considerable interest. The PilZ domain was the first c-di-GMP receptor to be predicted and identified. However, every PilZ domain binds c-di-GMP with a different binding affinity. Intriguingly, a noncanonical PilZ domain has recently been found to serve as a mediator to link FimXEAL to the PilB or PilT ATPase to control the function of type IV pili (T4P). It is thus essential to determine the structure of the FimXEAL-PilZ complex in order to determine how the binding of c-di-GMP to the FimXEAL domain induces conformational change of the adjoining noncanonical PilZ domain, which may transmit information to PilB or PilT to control T4P function. Here, the preparation and preliminary X-ray diffraction studies of the XccFimXEAL-c-di-GMP and XccFimXEAL-c-di-GMP-XccPilZ complexes from Xcc (Xanthomonas campestris pv. campesteris) are reported. Detailed studies of these complexes may allow a more thorough understanding of how c-di-GMP transmits its effects through the degenerate EAL domain and the noncanonical PilZ domain.